Clinical and laboratory evaluation of hyperlipemic and hypothyroid patients - Castro, Ana Valéria Barros de [UNESP]; Bononi, Alexandra Procópio [UNESP]; Aragon, Flávio Ferrari [UNESP]; Padovani, Carlos Roberto [UNESP]; Nogueira, Célia Regina [UNESP]; Mazeto, Glaucia Maria Ferreira da Silva [UNESP]; Pimenta, Walkyria de Paula [UNESP] (Sociedade Brasileira de Cardiologia (SBC), 2001)
OBJECTIVE: To determine the frequency of hypothyroidism in a sample of hyperlipemic patients and evaluate clinical and laboratory factors indicative of thyropathy among them. METHODS: Fifty-one hyperlipemic patients, grouped according to an earlier or recent diagnosis of their thyroid function into euthyroid and hypothyroid, were evaluated with clinical and laboratory examinations of blood levels of free T4 and TSH (by radioimmunoassay). Patients were on average 46.8±11.7 years old, predominantly of the female sex (62.5%); 31% had a previous diagnosis of hypothyroidism and were under treatment with thyroxin. RESULTS: Fourteen three percent of patients analyzed had hypothyroidism, which had not been detected before. Differentiating attributes of the groups analyzed were: a predominance of females among the hypothyroid patients and a higher HDL serum concentration among those recently diagnosed. CONCLUSION: In the present study, new cases of hypothyroidism in hyperlipemic patients were a frequent occurrence, yet few clinical and laboratory data except tests evaluating free T4 and TSH in the blood indicated which patients had thyroid dysfunction.
Keywords: hypothyroidism; hyperlipemia; dyslipemia